The inhibition of voltage-gated H⁺ channel (HVCN1) induces acidification of leukemic Jurkat T cells promoting cell death by apoptosis - Asuaje, Agustín (2017)
Cellular energetic deregulation is widely known to produce an overproduction of acidic species in cancer cells. This acid overload must be counterbalanced with a high rate of H⁺ extrusion to maintain cell viability. In this sense, many H⁺ transporters have been reported to be crucial for cell survival and proposed as antineoplastic target. By the way, voltage-gated proton channels (Hv1) mediate highly selective H⁺ outward currents, capable to compensate acid burden in brief periods of time. This structure is canonically described acting as NADPH oxidase counterbalance in reactive oxygen species production. In this work, we show, for the first time in a oncohematologic cell line, that inhibition of Hv1 channels by Zn2⁺ and the more selective blocker 2-(6-chloro-1Hbenzimidazol-2-yl)guanidine (ClGBI) progressively decreases intracellular pH in resting conditions. This acidification is evident minutes after blockade and progresses under prolonged exposure (2, 17, and 48 h), and we firstly demonstrate that this is followed by cell death through apoptosis (annexin V binding). Altogether, these results contribute strong evidence that this channel might be a new therapeutic target in cancer.